2004
DOI: 10.1590/s1516-89132004000300018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Apis mellifera Carniolan and Africanized honey bees in royal jelly production

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 7 publications
2
11
0
3
Order By: Relevance
“…The lower nuclei was composed of five combs and the upper, of four combs and a frame with cell cups spaced on cell bars (Mouro & Toledo, 2004). This cup bar frame consisted of 28 acrylic cups, 14 at the upper bar and 14 at the lower bar.…”
Section: Methodsmentioning
confidence: 99%
“…The lower nuclei was composed of five combs and the upper, of four combs and a frame with cell cups spaced on cell bars (Mouro & Toledo, 2004). This cup bar frame consisted of 28 acrylic cups, 14 at the upper bar and 14 at the lower bar.…”
Section: Methodsmentioning
confidence: 99%
“…Another very important factor to be considered is the selection of the Africanized honeybee colonies (MOURO; TOLEDO, 2004;MOURO, 2005;FAQUINELLO et al, 2011) associated with supplementation as the key to increase royal jelly production, and quality and consequently guarantee more profits to the beekeepers too (SEREIA et al, 2010).…”
Section: Physicochemical Quality Of Royal Jelly Samplesmentioning
confidence: 99%
“…Mouro and Toledo [40] had higher royal jelly productions in hybrid Carniolan in relation to Africanized honeybee colonies. However, royal jelly production increased 109.19% in the first generation after performing the selection in Africanized honeybees.…”
Section: Chronology Of Selection For Royal Jelly Productionmentioning
confidence: 87%
“…Sereia et al [39] concluded that the average amount of royal jelly deposited every 68 h per cup was higher when supplemented with isolated soy protein, brewer's yeast, palm oil, and linseed oil. Some studies reported variation in royal jelly production of Apis mellifera L. Africanized honeybees from 188 to 234 mg/cup [10,35,40]. Toledo and Mouro [35] stated that the amount of royal jelly obtained per cup varies with the time that is left within the colony and obtained average of 253 mg/cup for Africanized and 198 mg/cup for Carniolian honeybees.…”
Section: Factors Influencing Royal Jelly Productionmentioning
confidence: 99%